Analisis Model Tarikan Pergerakan Sekolah Di Kota Palangka Raya: Analysis Of School Trip Attraction In Palangka Raya City - Sitinjak, Tarita Aprilani (Media Ilmiah Teknik Sipil, 2024)
The school zone is a land use that can create the trip attraction. The purpose of this study is to model the trip attraction and to analysis the factors that most influence attraction to the Catholic school area in Palangka Raya. The study was conducted at four schools in one zone. Primary data, i.e. the number of vehicles entering the school premises, was obtained through direct observation in the target schools. Secondary data was obtained through documentation and interviews with the operators of the schools. The collected data was analysed using the linear regression statistical method assisted by SPSS software version 25. All variables involved, i.e. number of students, number of teachers, number of school benches, class capacity and class area, are strongly correlated with the variable 'traffic volume'. From the linear regression analysis, the number of students is the independent variable that is highly correlated and significantly influence the trip attraction, as shown by the value of r=0.99 and R2 = 0.998. The model of physical activity attractiveness in this study is Y = -10.686 + 0.934X1. The results of this study contribute to education field especially in transportation, as they support the theory that the number of students significantly influences the trip attraction in school land use